1980
DOI: 10.3382/ps.0590095
|View full text |Cite
|
Sign up to set email alerts
|

Source of Protein Affecting the Vitamin B6 Requirement of Chicks

Abstract: Two experiments were conducted to determine the effect of different plant protein meals on the vitamin B 6 requirement of broiler chicks. Soybean meal, cottonseed meal, and safflower meal were added to semipurified rations deficient in vitamin B,j to contribute 60% of the protein (Experiment 1) or 40% of the protein (Experiment 2). The rest of the protein in the rations was supplied by isolated soy protein. Vitamin B e was added at 0, .5, and 5.0 mg/kg levels.No response to vitamin B 6 supplementation was note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Daghir and Shah (1973) fed chicks diets containing 15, 20, or 25% protein and found that the amount of pyridoxine required to increase body weight and feed efficiency increased with increasing dietary protein. Kazemi and Kratzer (1980) fed chicks diets containing soybean meal, cottonseed meal, or safflower meal as the primary protein source. The chicks fed diets containing soybean meal required more pyridoxine to maximize growth, even though the chemical analysis showed that soybean meal contained the highest pyridoxine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Daghir and Shah (1973) fed chicks diets containing 15, 20, or 25% protein and found that the amount of pyridoxine required to increase body weight and feed efficiency increased with increasing dietary protein. Kazemi and Kratzer (1980) fed chicks diets containing soybean meal, cottonseed meal, or safflower meal as the primary protein source. The chicks fed diets containing soybean meal required more pyridoxine to maximize growth, even though the chemical analysis showed that soybean meal contained the highest pyridoxine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of SPI was reported to be lower than that of casein, with a pro tein efficiency ratio of 1.82 (73% of casein) as assayed using growing rats [13]. However, the results of nitrogen balance studies carried out with young male students indi cated that SPI was of good quality and that the amount of this protein needed to maintain N balance was similar to that for proteins of animal origin such as egg, milk and meat [16,17], Kazemi and Kratzer [6] hypothesized that the rason why the source of dietary protein significantly influenced the requirement of vitamin B6 in chicks could be the difference in the amino acid composition. The con tent of methionine, the first limiting amino acid of SPI, is only 44% of that of casein, and the total sulfur amino acid content of the former is about 76% of the latter.…”
Section: Discussionmentioning
confidence: 98%
“…However, little is known about whether different sources of dietary protein affect the requirement for vita min Bg. Kazemi and Kratzer [6] observed that chicks fed with a soybean diet required more vitamin Bg for opti mum growth than did those fed with a safflower or cotton seed diet. On the other hand, Kretsch et al [7] found that more vitamin Bg was required to normalize xanthurenic acid excretion in vitamin-Bg-depleted young women fed animal protein than in subjects fed plant protein.…”
mentioning
confidence: 99%